(3WHbGJ abgGA Gdjef hQDSGA Gdjefs - (3YeQ Hf Ydj Hf SeQI Hf GdMSjf GdLYOj,J (B586 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CdgefG MeOg hCagefG dSDGdg hbUOg s
(3BNQgG (B:s
(3hefge Gdabjg YHO Gddg GdVLGYi , eScfg bQjI VLGYI , QMege Gddg CLeYjf , hfaYfG Hge hHYdhege Bejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HBNQgG cQSJGf HNW MOjK SfI (B1197 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B55s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN eTQa YHO GdcQje GdNGUI HJYR s
Keywords: (3GdJGQjNs